SELECTED THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR THE STUDY OF NATIONAL INTERESTS IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article discusses historical and semantic problems necessary to clarify the concept of national interests in the conditions of the Kyrgyz Republic, the meaning of the words “nation” and “interests” applicable for analysis in this direction. As a result of the analysis, a definition of national interests acceptable for the Kyrgyz Republic is proposed.
Keywords: nation; nationality; ethnic group; Kyrgyzstan; state; people; native language